Nitrogen-doped carbon nanomaterial, preparation method thereof and application as negative electrode material

By using nitrogen-doped carbon nanomaterials as negative electrode materials in sodium ion batteries, the problem of low reversible capacity caused by small layer spacing of commercial graphite negative electrode materials in sodium ion batteries is solved, and efficient sodium ion storage and transmission is achieved, significantly improving the The electrochemical properties of the battery.

CN115692652BActive Publication Date: 2024-12-27HUNAN JIDIAN SPECIAL ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211314090.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2024-12-27
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The commercial graphite anode materials in existing sodium ion batteries exhibit low reversible capacity due to their small layer spacing and large sodium ion radius, which are difficult to meet the needs of large-scale applications.

Method used

Using nitrogen-doped carbon nanomaterial as the negative electrode material, it is prepared by mixing, freeze-drying and pyrolysis of sodium carboxymethylcellulose and graphite phase carbon nitride to form a two-dimensional carbon nanosheet-like structure and a graded porous structure, expanding the layer spacing and improve conductivity.

Benefits of technology

It significantly improves the first week of Coulomb efficiency, low-potential platform specific capacity, reversible specific capacity and rate performance of sodium ion batteries, improves cycling performance, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115692652B_ABST
    Figure CN115692652B_ABST
Patent Text Reader

Abstract

The present invention provides a nitrogen-doped carbon nanomaterial, a preparation method thereof, and an application thereof as a negative electrode material. The present invention mixes a precursor sodium carboxymethyl cellulose solution with graphite phase carbon nitride, prepares a composite film by freeze-drying technology, and then pyrolyzes the composite film at high temperature to form nitrogen-doped two-dimensional carbon nanosheets. In the present invention, the graphite phase carbon nitride is used as a template to provide a rich nitrogen source on the one hand, and to assist the formation of a two-dimensional sheet structure of the carbon nanosheet by utilizing a two-dimensional layered structure on the other hand. The present invention also provides a sodium ion battery based on nitrogen-doped carbon nanomaterials as negative electrode materials, which exhibits a high first-cycle coulombic efficiency, low potential platform specific capacity, reversible specific capacity, and superior rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a nitrogen-doped carbon nanomaterial and a preparation method thereof, and an application thereof as a negative electrode material for a sodium ion battery. Background Art

[0002] The rapid increase in the cost of lithium-ion batteries, which are used in large-scale applications in electric vehicles, portable electronic devices, and smart grids, has created an urgent need to find alternative energy sources to meet the growing demand.

[0003] Due to the abundance of sodium resources and the low cost of sodium-ion batteries, sodium-ion batteries are expected to become a new type of energy storage device that can replace lithium-ion batteries for large-scale applications. However, commercial graphite anodes have a smaller interlayer spacing (0.3354nm) and the radius of sodium ions (0.102nm) is larger than the radius of lithium ions (0.076nm), resulting in lower reversible capacity of graphite anodes in sodium-ion batteries. Therefore, the development of high-performance anode materials is the key to improving the performance of sodium-ion batteries and realizing large-scale applications of sodium-ion batteries. Summary of the invention

[0004] Based on this, it is necessary to provide a nitrogen-doped carbon nanomaterial and a preparation method thereof and an application as a negative electrode material in a sodium ion battery, which can enable the sodium ion battery to exhibit a higher first-cycle coulombic efficiency, low-potential platform specific capacity, reversible specific capacity and superior rate performance and cycle performance.

[0005] The present invention adopts the following technical solution:

[0006] The present invention provides a nitrogen-doped carbon nanomaterial, which is mainly prepared by suspension mixing, freeze drying and pyrolysis of sodium carboxymethyl cellulose hydrogel and graphite phase carbon nitride, and has a two-dimensional carbon nanosheet structure and a hierarchical porous structure. Among them, the atomic percentage of nitrogen element is 1.8-5.0 at.% (preferably 2.0-3.0 at.%), and the interlayer spacing is 0.367-0.388 nm; the hierarchical porous structure includes micropores and mesopores, the pore diameter of the micropores is 0.5-1.5 nm, and the pore diameter of the mesopores is 2-3 nm.

[0007] The invention provides a preparation method of nitrogen-doped carbon nanomaterials, comprising the following steps: taking sodium carboxymethyl cellulose as a precursor, dissolving it in deionized water, stirring for 2-4 hours to form a hydrogel; adding graphite phase carbon nitride to the hydrogel, wherein the mass ratio of the graphite phase carbon nitride to the sodium carboxymethyl cellulose is (0.5-1.5):1, and stirring for 2-6 hours to form a suspension; transferring the suspension to a freeze dryer, freeze drying at -40-60°C for 48-72 hours to obtain a sponge-like composite film; heating the sponge-like composite film to a pyrolysis temperature of 900-1200°C in an argon atmosphere, and keeping the temperature for 1-2 hours to obtain a carbonized product; grinding, acid washing, and water washing the carbonized product for multiple times, and drying at a high temperature of 100-120°C to obtain the product.

[0008] In some embodiments, the preparation method of the graphite phase carbon nitride comprises the following steps: obtaining a raw material for preparing graphite phase carbon nitride, wherein the raw material is selected from one or more of melamine, urea, thiourea, and dicyandiamide, placing the raw material under an argon atmosphere, heating the temperature to 550±50°C, and keeping the temperature for 4 hours. Preferably, the mass ratio of the graphite phase carbon nitride to the sodium carboxymethyl cellulose is (0.5-1):1.

[0009] In some embodiments, the heating rate of the pyrolysis temperature is 1-5°C / min.

[0010] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is prepared by using the above-mentioned nitrogen-doped carbon nanomaterial. Specifically, the negative electrode sheet comprises a negative electrode current collector and a negative electrode slurry disposed on the negative electrode current collector, wherein the negative electrode slurry is mainly a mixture of nitrogen-doped carbon nanomaterial, a conductive agent, a binder and a solvent.

[0011] The electrolyte contains an electrolyte sodium salt and an organic solvent, wherein the electrolyte sodium salt is at least selected from sodium hexafluorophosphate (NaPF 6 ) or sodium perchlorate (NaClO 4 ), wherein the organic solvent is selected from one or more of ethylene glycol dimethyl ether (DME), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and diethyl carbonate (DEC).

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] (1) The cellulose derivative sodium carboxymethyl cellulose is used as a precursor. The preparation process is simple, the cost is low, the source is very abundant, and the surface contains a large number of hydrophilic functional groups. It can interact with nitrogen-rich graphite phase carbon nitride through hydrogen bonds to form a structurally stable network macromolecule. Even after carbonization, it can still maintain a strong interaction with the active carrier.

[0014] (2) The graphite phase carbon nitride prepared by the present invention has a unique two-dimensional layered structure and rich nitrogen elements. As a template, it can inhibit the accumulation and agglomeration of sodium carboxymethyl cellulose particles during the pyrolysis process and assist in the formation of a two-dimensional sheet structure of carbon nanosheets. At a temperature of 600 to 700°C, the graphite phase carbon nitride completely decomposes and releases nitrogen-containing gas, and the doping reaction forms a nitrogen-doped two-dimensional carbon nanosheet material.

[0015] (3) The nitrogen-doped carbon nanomaterial prepared by the present invention has a two-dimensional carbon nanosheet structure and a porous structure, which is conducive to increasing the full contact between the electrode and the electrolyte, shortening the transmission path of sodium ions, and improving the conductivity. The appropriate nitrogen doping content (2.0-3.0 at.%) can not only improve the conductivity of the material, but also provide more active sites for sodium ion storage. Too high nitrogen doping content is not conducive to the formation of local graphitization structure and reduces the conductivity of the material; too low doping content leads to fewer active sites and reduces the storage capacity of sodium ions. The enlarged interlayer spacing, the interlayer spacing can reach up to 0.388nm and the hierarchical porous structure is mainly composed of micropores and mesopores, the micropore diameter is 0.5-1.5nm, and the mesopore diameter is 2-3nm. This structure is conducive to the easy insertion and removal of sodium ions from the interlayer, accelerates the transmission of sodium ions, and can buffer the volume expansion caused by sodium ions during the charging and discharging process, effectively improving the electrochemical performance of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The scanning electron microscope images of nitrogen-doped carbon nanomaterials in some test examples are shown in FIG. 1 , wherein (a) corresponds to the nitrogen-doped carbon nanomaterial prepared in Example 1, and (b) corresponds to the material prepared in Example 1.

[0017] Figure 2 TEM images of nitrogen-doped carbon nanomaterials in some test examples; (a) corresponds to the nitrogen-doped carbon nanomaterial prepared in Example 1, and (b) corresponds to the material prepared in Example 1. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0019] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0020] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0021] Example 1

[0022] This embodiment provides a method for preparing a nitrogen-doped carbon nanomaterial, comprising the following steps:

[0023] S1, dissolve 1.0 g of sodium carboxymethyl cellulose in deionized water and stir for 2 h to form a uniform and transparent hydrogel.

[0024] S2, adding 1.0 g of graphite phase carbon nitride to the hydrogel of step S1, stirring for 4 hours to form a uniform suspension. The graphite phase carbon nitride in this step is prepared by using melamine as a raw material, heating to 550° C. at a rate of 2° C. / min and keeping the temperature for 4 hours in an argon atmosphere.

[0025] S3, transferring the suspension prepared in step S2 to a freeze dryer, and freeze drying it at -60°C for 48 hours to obtain a sponge-like composite film.

[0026] S4, heating the sponge-like composite film prepared in step S3 to a pyrolysis temperature of 1050° C. at a rate of 2° C. / min under an argon atmosphere, and keeping the temperature for 2 hours to obtain a carbonized product.

[0027] S5, grinding, acid washing (conventional acid such as hydrochloric acid) and water washing the product after carbonization in step S4 for multiple times, and drying at 110° C. to obtain the nitrogen-doped two-dimensional carbon nanosheet material prepared in Example 1.

[0028] Example 2

[0029] This embodiment provides a method for preparing nitrogen-doped carbon nanomaterials. The raw materials and process steps are basically the same as those in Embodiment 1, with the only difference being that the pyrolysis temperature in step S4 is 900°C.

[0030] Example 3

[0031] This embodiment provides a method for preparing nitrogen-doped carbon nanomaterials. The raw materials and process steps are basically the same as those in Embodiment 1, with the only difference being that the pyrolysis temperature in step S4 is 1200°C.

[0032] Comparative Example 1

[0033] This comparative example provides a method for preparing a negative electrode material, comprising the following steps:

[0034] S1, dissolve 1.0 g of sodium carboxymethyl cellulose in deionized water and stir for 2 h to form a uniform and transparent hydrogel.

[0035] S2, transferring the hydrogel prepared in step S1 to a freeze dryer, and freeze drying it at -60°C for 48 hours to obtain a transparent film.

[0036] S3, heating the transparent film prepared in step S2 to a pyrolysis temperature of 1050° C. at a rate of 2° C. / min under an argon atmosphere, and keeping the temperature for 2 hours to obtain a carbonized product.

[0037] S4, grinding, acid-washing, and water-washing the product after carbonization in step S3 for multiple times, and drying at a high temperature of 110° C. to obtain the negative electrode material prepared in comparative example 1.

[0038] The materials obtained in Example 1 and Comparative Example 1 were characterized by scanning electron microscopy and transmission electron microscopy. Figure 1 and 2 shown.

[0039] As can be seen from Figure 1, the material prepared in Example 1 exhibits a carbon nanosheet structure with a rough and wrinkled surface. The nitrogen-doped carbon nanomaterial with a carbon nanosheet structure is beneficial to increase the contact area between the electrode and the electrolyte, allowing the electrolyte to fully penetrate into the electrode, reducing the transmission distance of sodium ions, and improving the conductivity of ions. The material prepared in Comparative Example 1 is mainly composed of irregular nanoparticles stacked to form a block structure.

[0040] Figure 2 The high-resolution image further reveals its microstructure. The microstructure of the material prepared in Example 1 is a partially graphitized graphene-like structure. By using DigitalMicrograph software to calculate the plane spacing of the graphene layer, the interlayer distance is significantly expanded to 0.388nm. Nitrogen-doped carbon nanomaterials have a hierarchical porous structure, which is mainly composed of micropores and mesopores. The micropore diameter is 0.5-1.5nm, and the mesopore diameter is 2-3nm. The enlarged interlayer spacing is conducive to the embedding and extraction of sodium ions, and accelerates the transmission of ions and electrons, thereby improving the low-potential platform specific capacity. The microstructure of the negative electrode material prepared in Comparative Example 1 is a highly disordered amorphous structure.

[0041] The specific surface area and pore size distribution of the nitrogen-doped carbon nanomaterials prepared in Examples 1 to 3 and the material prepared in Comparative Example 1 were further tested using a nitrogen adsorption-desorption method. The results are shown in Table 1 below:

[0042] Table 1 Test parameters of materials prepared in Examples 1 to 3 and Comparative Example 1

[0043]

[0044] The nitrogen-doped carbon nanomaterials prepared in Examples 1 to 3 and the material prepared in Comparative Example 1 were further used as negative electrode materials, and acetylene black and sodium alginate were added with an appropriate amount of deionized water in a mass ratio of 8:1:1, mixed evenly, and stirred for at least 6 hours. The uniform slurry was coated on an aluminum foil current collector, vacuum dried and cut to form a negative electrode sheet. The prepared negative electrode sheet was mixed with a metal sodium sheet, a glass fiber separator and an electrolyte (with 1.0 mol NaPF 6 or NaClO 4 The mixed solution of ethylene glycol dimethyl ether (dissolved in 1L volume) was assembled into a CR2032 button battery in a vacuum glove box filled with Ar atmosphere, and constant current charge and discharge test was performed:

[0045] The test voltage range is 0-2.5V, the current density is 0.05A / g, and the first week coulombic efficiency, low potential platform specific capacity and reversible specific capacity of the sodium ion battery prepared in each embodiment and comparative example are obtained; the current density is 0.05, 0.1, 0.2, 0.5, 1, 2 and 5A / g, and the rate performance of the sodium ion battery prepared in each embodiment and comparative example is obtained; when the current density is 0.5A / g, the charge and discharge cycle is 2000 weeks, and the reversible specific capacity retention rate of the sodium ion battery prepared in each embodiment and comparative example is obtained. The test results are shown in Tables 2 and 3 below:

[0046] Table 2 Performance test of Examples 1 to 3 and Comparative Example 1 as negative electrode materials (NaPF 6 )

[0047]

[0048] It can be seen from Table 2 above that compared with Comparative Example 1, the first-week coulombic efficiency, low-potential platform specific capacity, reversible specific capacity and rate cycling performance of the sodium ion batteries prepared in Examples 1-3 using nitrogen-doped carbon nanomaterials as negative electrode materials are significantly improved, indicating that the nitrogen-doped carbon nanomaterials prepared in the above test examples rely on hierarchical porous structure, appropriate nitrogen doping content and enlarged interlayer spacing to improve the electrochemical performance of sodium ion batteries.

[0049] At the same time, it can be seen that the pyrolysis temperature in the preparation method of the nitrogen-doped carbon nanomaterials of Examples 1 to 3 has a certain influence on the electrochemical performance of the prepared sodium ion battery.

[0050] Furthermore, the optimal parameter range of the pyrolysis temperature was determined to be 1000-1100°C through experiments, which is conducive to the preparation of sodium ion battery negative electrode materials with superior electrochemical properties.

[0051] Table 3 Performance test of Examples 1 to 3 and Comparative Example 1 as negative electrode materials (NaClO 4 )

[0052]

[0053] From the comparative analysis of the data in Table 3 and Table 2 above, it can be concluded that the use of different electrolyte sodium salts has little effect on the electrochemical performance of the prepared sodium ion battery, but the comprehensive comparison shows that the electrolyte prepared with sodium hexafluorophosphate as the electrolyte sodium salt has better performance and can be given priority.

[0054] Example 4

[0055] This embodiment provides a method for preparing a nitrogen-doped carbon nanomaterial. The raw materials and process steps of the preparation are basically the same as those of Example 1, with the only difference being that the raw material for preparing graphite phase carbon nitride is urea.

[0056] Example 5

[0057] This embodiment provides a method for preparing a nitrogen-doped carbon nanomaterial. The raw materials and process steps of the preparation are basically the same as those of Example 1, except that the raw material for preparing graphite phase carbon nitride is thiourea.

[0058] Example 6

[0059] This embodiment provides a method for preparing a nitrogen-doped carbon nanomaterial. The raw materials and process steps for preparing the carbon nitride are substantially the same as those of Embodiment 1, except that the raw material for preparing the carbon nitride is dicyandiamide.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a nitrogen-doped carbon nanomaterial. The raw materials and process steps of the preparation are basically the same as those of Example 1, except that an equal amount of cellulose is used to replace sodium carboxymethyl cellulose.

[0062] The materials prepared in Examples 4 to 6 and Comparative Example 2 were tested according to the above test method, and the results are shown in Tables 4 and 5 below:

[0063] Table 4 Test parameters of materials prepared in Examples 4 to 6 and Comparative Example 2

[0064]

[0065] Table 5 Performance test of Examples 4 to 6 and Comparative Example 2 as negative electrode materials

[0066]

[0067] It can be seen from the experimental results of the embodiments of the present invention and the comparative examples that the sodium ion battery finally prepared by the present invention has at least the following five advantages:

[0068] (1) With the assistance of graphite phase carbon nitride, the prepared nitrogen-doped carbon nanomaterial as a negative electrode material exhibits a more obvious platform specific capacity at low potential (<0.1V) in sodium ion battery applications. In particular, the present invention can provide a platform specific capacity of up to 124.4mAh / g.

[0069] (2) It has a high reversible specific capacity and first-cycle coulombic efficiency. In particular, the reversible specific capacity of the sodium ion battery prepared by using the nitrogen-doped carbon nanomaterial of Example 1 of the present invention as the negative electrode material is as high as 304.7 mAh / g and the first-cycle coulombic efficiency is as high as 80.0%.

[0070] (3) Excellent cycle performance. In particular, the sodium ion battery prepared by using the nitrogen-doped carbon nanomaterial of Example 1 of the present invention as the negative electrode material has a capacity retention rate of up to 90.9% after 2000 cycles.

[0071] (4) Good rate performance. In particular, at a current density of 0.05 A / g, the reversible specific capacity of the sodium ion battery prepared by using the nitrogen-doped carbon nanomaterial of Example 1 as the negative electrode material is as high as 304.7 mAh / g, and even if the current density rises to 5.0 A / g, the capacity can still be maintained at 197.6 mAh / g.

[0072] (5) Electrochemical performance is affected by the structure of the negative electrode material regulated by the nitrogen doping content. The present invention mainly controls the nitrogen doping content by controlling the pyrolysis temperature to optimize the structure of the two-dimensional carbon nanosheets. The nitrogen-doped carbon nanomaterials prepared at different pyrolysis temperatures are used as negative electrode materials in sodium ion batteries and exhibit different electrochemical properties.

[0073] In addition, it is worth mentioning that:

[0074] The present invention actually provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The negative electrode sheet comprises a negative electrode current collector and a negative electrode slurry disposed on the negative electrode current collector; the negative electrode slurry comprises a nitrogen-doped carbon nanomaterial, a conductive agent, a binder, and a solvent.

[0075] Among them, the nitrogen-doped carbon nanomaterial in the embodiment of the present invention is used as the negative electrode material, and its microstructure has the following characteristics: an enlarged interlayer spacing, which can reach 0.367-0.388nm; the graded porous structure is mainly composed of micropores and mesopores, the pore size of the micropores is 0.5-1.5nm, and the pore size of the mesopores is 2-3nm.

[0076] The preparation method of the nitrogen-doped carbon nanomaterial in the embodiment of the present invention comprises the following steps: a. taking sodium carboxymethyl cellulose as a precursor, dissolving it in deionized water, stirring for 2 to 4 hours to form a hydrogel; b. adding graphite phase carbon nitride to the hydrogel, wherein the mass ratio of graphite phase carbon nitride to sodium carboxymethyl cellulose is 0.5 to 1.5:1, and stirring for 2 to 6 hours to form a suspension; c. transferring the suspension to a freeze dryer, freeze-drying it at -40 to 60°C for 48 to 72 hours to obtain a sponge-like composite film; d. heating the sponge-like composite film to a pyrolysis temperature of 900 to 1200°C in an argon atmosphere, and keeping it warm for 1 to 2 hours to obtain a carbonized product; e. grinding, pickling, and washing the carbonized product for multiple times, and drying it at a high temperature of 100 to 120°C to obtain the product.

[0077] The electrolyte is not particularly limited in the present invention, and a conventional electrolyte can be used. For example, the electrolyte may contain an electrolyte sodium salt and an organic solvent, wherein the electrolyte sodium salt may be sodium hexafluorophosphate (NaPF 6 ) or sodium perchlorate (NaClO 4 ), the organic solvent may be one or more selected from ethylene glycol dimethyl ether (DME), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and diethyl carbonate (DEC).

[0078] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nitrogen-doped carbon nanomaterial, characterized in that: The nitrogen-doped carbon nanomaterial is prepared by suspension mixing, freeze drying and pyrolysis of sodium carboxymethyl cellulose hydrogel and graphite phase carbon nitride under an argon atmosphere at a pyrolysis temperature of 900 to 1200° C., and has a two-dimensional carbon nanosheet structure and a hierarchical porous structure. The nitrogen atomic percentage of the nitrogen doped carbon nanomaterial is 1.8 to 5.0 at.%, and / or the interlayer spacing of the nitrogen doped carbon nanomaterial is 0.367 to 0.388 nm.

2. The nitrogen-doped carbon nanomaterial according to claim 1, characterized in that: The hierarchical porous structure includes micropores and mesopores, the pore diameter of the micropores is 0.5-1.5 nm, and the pore diameter of the mesopores is 2-3 nm.

3. A method for preparing a nitrogen-doped carbon nanomaterial as claimed in claim 1 or 2, characterized in that: The steps include: Sodium carboxymethyl cellulose was used as a precursor, dissolved in deionized water, and stirred to form a hydrogel; adding graphite phase carbon nitride into the hydrogel and stirring to form a suspension; freeze-drying the suspension to obtain a sponge-like composite film; The sponge-like composite film is heated to a pyrolysis temperature of 900 to 1200° C. in an argon atmosphere, and kept warm for reaction to obtain a carbonized product; The carbonized product is ground, washed and dried to obtain the product.

4. The method for preparing nitrogen-doped carbon nanomaterials according to claim 3, characterized in that: Obtain a raw material for preparing graphite phase carbon nitride, wherein the raw material is selected from one or more of melamine, urea, thiourea and dicyandiamide, place the raw material under an argon atmosphere, heat it to 550±50° C., and keep it warm for reaction to obtain the product.

5. The method for preparing nitrogen-doped carbon nanomaterials according to claim 4, characterized in that: The mass ratio of the graphite phase carbon nitride to the sodium carboxymethyl cellulose is (0.5-1.5):

1.

6. The method for preparing nitrogen-doped carbon nanomaterials according to any one of claims 3 to 5, characterized in that: The heating rate of the pyrolysis temperature is 1-5°C / min.

7. Use of the nitrogen-doped carbon nanomaterial according to claim 1 or 2 as a negative electrode material for a sodium ion battery.

8. A sodium ion battery, characterized in that: It comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate adopts the nitrogen-doped carbon nanomaterial according to claim 1 or 2 as the negative electrode material.

9. The sodium ion battery according to claim 8, characterized in that: The negative electrode sheet is prepared from a negative electrode current collector and a negative electrode slurry disposed on the negative electrode current collector, and the negative electrode slurry is mainly formed by mixing the nitrogen-doped carbon nanomaterial according to claim 1 or 2, a conductive agent, a binder and a solvent.

10. The sodium ion battery according to claim 8 or 9, characterized in that: The electrolyte contains electrolyte sodium salt, and the electrolyte sodium salt is at least selected from one of sodium hexafluorophosphate and sodium perchlorate.